Comparing Clinical Outcomes and Health Care Utilization: Telehealth Versus Traditional Care at US Rural Hemodialysis Units - Mariam Charkviani, MD; Lagu A. Androga, MD; Arvind K. Garg, MD; Priya Ramar, MPH; Rachel H. Amundson, MHA; Lisa E. Vaughan, MS; Ziad Zoghby, MD; Robert C. Albright, Jr., DO (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2025)
Objective: To determine whether novel dialysis delivery models, such as telehealth visits combined with face-to-face visits in a hybrid model (telehealth hybrid model), positively influence clinical outcomes and healthcare utilization. Patients and Methods: This retrospective cohort study compares the rates of emergency department visits, hospitalizations, and Medicare established hemodialysis quality metrics before and after implementation of a telehealth hybrid model focused among rural populations in regions served by the Mayo Clinic dialysis system between January 1, 2020, to December 31, 2020, versus face-to-face visits alone before implementation of the program from January 1, 2019, to December 31, 2019. In addition, we used a standardized anonymous survey to examine patient perspectives toward the implementation of telehealth at the dialysis units. Results: No significant differences in health care utilization outcomes (emergency department visits: Incidence rate ratios, 95% CI, 0.87 (0.62-1.22); P=.41; hospitalizations: Incidence rate ratios, 95% CI, 0.92 (0.63-1.35); P=.68) or clinical outcomes (abnormal laboratory measures) between the telehealth and standard care groups were observed. Patient satisfaction with telehealth was high, with 90% reporting successful video visits. Conclusion: Our study provides evidence suggesting that the telehealth hybrid model can deliver nephrology care comparable to traditional care models in in-center dialysis without negatively impacting clinical outcomes, health care utilization, or patient satisfaction. Further research is necessary to confirm these results in other settings and to explore the long-term impacts of such hybrid care models.